Magnesium and the Saleability of Your Product - Dow Chemical Company (1952)
Black and white print advertisement for Dowmetal, a magnesium alloy manufactured and sold by the Dow Chemical Company. Describes how the use of Dowmetal magnesium material can save manufacturers money in production and can lead to more saleable products. The material is advertised as lightweight, strong, corrosion-resistant, and able to be shaped and produced in a variety of forms. Depicts a hand holding a wad of money, pointing at a round machine. Includes a brief description of Dowmetal's application to the United States' defense effort. The Dowmetal logo, a hand holding a winged ingot of magnesium, is located in the bottom right of the advertisement. Found on page 67 of Time Magazine, April 21, 1952 issue.
Keywords: Advertising; Dow Chemical Company; Advertising, Industrial; Chemical Industry; Magnesium alloys; Mineral industries